2007
DOI: 10.1097/wco.0b013e328172d661
|View full text |Cite
|
Sign up to set email alerts
|

The relation between white-matter lesions and cognition

Abstract: White-matter lesions cannot be considered as mere incidental findings, at least in patients who show severe lesions. The pathogenesis of white-matter lesions must be clarified further and strategies found to delay their progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
112
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 45 publications
5
112
0
2
Order By: Relevance
“…However, the sole presence of WMH cannot be considered as a factor of cognitive deterioration. Rather, it is likely that a threshold in white matter lesion load exists, beyond which cognitive decline is caused, and that this threshold can vary depending on host factors and the presence of concomitant lesions [23]. Although cognitive dysfunction represents an exclusion criterion in the diagnosis of MSA, several studies reported frontal lobe-associated cognitive dysfunction in patients with MSA, by means of comprehensive neuropsychological testing [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the sole presence of WMH cannot be considered as a factor of cognitive deterioration. Rather, it is likely that a threshold in white matter lesion load exists, beyond which cognitive decline is caused, and that this threshold can vary depending on host factors and the presence of concomitant lesions [23]. Although cognitive dysfunction represents an exclusion criterion in the diagnosis of MSA, several studies reported frontal lobe-associated cognitive dysfunction in patients with MSA, by means of comprehensive neuropsychological testing [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…First, WML is associated with reduced cognitive functioning in MCI. It is widely accepted that a severe grade of WML has a detrimental impact on cognitive functioning including executive function, attention, processing speed, and global cognition (Jokinen, Lipsanen, & Schmidt, 2012;Meier et al, 2012;Pantoni, Poggesi, & Inzitari, 2007;Prins & Scheltens, 2015;Xiong & Mok, 2011). Second, the location or the spatial distribution of the WML has a differential impact on cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a major risk factor for cerebral small vessel disease (cSVD),2 which in turn leads to brain damage that can be made visible on brain MRI. These imaging markers of cSVD are strongly associated with cognitive function 3, 4, 5, 6. Other types of hypertensive organ damage, such as cardiac and renal damages, have also been linked to lower cognitive function or increased risk of cognitive impairment 7, 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%